WOMEN'S LEADERSHIP IN THE VIEWS OF MUḤAMMAD AL-GHAZĀLĪ: Hermeneutical Analysis of The Hadith Narrated by Abū Bakrah - Moh Hasbulloh; Fathur Rozi; Budi Ichwayudi (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
This research is motivated by the existence of female leadership which is always in the spotlight in Islamic society where women are not worthy of being leaders for various reasons. One of them is a hadith narrated by Abī Bakrah regarding the leadership of Kisra which is considered a prohibition on women becoming leaders. This research involved library research which used written data sources. Moreover, this research also conducted the hermeneutic method with a socio-historical approach. The results of this research can be concluded that al-Ghazālī emphasized a specification for women who should not be entrusted with leadership duties by the Prophet Muḥammad saw, were women who did not meet the leadership requirements. Consequently, al-Ghazālī believed that this hadith could not be used as a basis for rejecting and accepting women as leaders.